PENDEKATAN ARTIFICIAL NEURAL NETWORK (ANN) UNTUK MENGKLASIFIKASIKAN HEWAN VETEBRATA MENGGUNAKAN KOHONEN SELF ORGANIZING MAP (SOM) - Tursina Tursina (Jurnal Informatika, 2013)
This research was proposes an approach to identifying vertebrates or invertebrates that premises Kohonen Self Organizing Map (SOM). SOM is one of the topology of the Artificial Neural Network (ANN).The network will be trained to classify five kinds of animals that will represent each class. Modeling requires 6 input neurons to input the characteristics of animals and 5 output neurons (according to the number of classes specified Key Word : Kohonen Self Organizing Map (SOM), Artificial Neural Network (ANN)